BS07 Urological disturbance and its neuroanatomical correlate in patients with chronic brainstem stroke. (May 2018) - Lee, Hye-Sun; Choi, Jeong Gue; Shin, Joon-Ho
Abstract : Introduction: Few studies have depicted urological disturbances among patients with chronic brainstem stroke, and little is known about the exact location of the micturition center or its role in humans. The aim of the present study was to retrospectively investigate urological disturbances and their neuroanatomical correlates among consecutively admitted patients with chronic brainstem stroke. Methods: Urodynamic studies, brain images, and urological symptoms questionnaires were reviewed from consecutive patients suffering from brainstem stroke, who had been admitted to a stroke unit at a rehabilitation hospital between June 1, 2013 and January 31, 2015. For further comparison, consecutive data from urodynamic studies of patients with upper cervical spinal cord injury (admitted to a hospital between January 1, 2008 and January 31, 2015) were reviewed. Results: Patients with chronic pontine stroke manifested more frequent detrusor underactivity, lower maximal detrusor pressure, and higher compliance than patients with upper cervical spinal cord injury. The most frequently involved lesions associated with detrusor underactivity were located around the central portion of the bilateral pons along the entire sagittal level. Urinary incontinence and symptoms associated with lower urinary tract dysfunction were reported in 10% and 95% of patients with brainstem stroke, respectively. No difference was found between genders or stroke subtypes in patients with brainstem stroke. Conclusion: The present study identified a relationship between chronic pontine stroke and detrusor underactivity. Thus, detrusor underactivity might be associated with lesions localized to central portions of the bilateral pons. The prevalence of lower urinary tract symptoms was also revealed to be high among patients with chronic brainstem stroke.